PEDAGOGICAL CONDITIONS OF THE PREPARATION OF FUTURE TEACHERS FOR MODELING THE LESSON IN THE CONTEXT OF VARIATIVITY OF THE PRIMARY EDUCATION - Nesterenko, Marina (Mountain School of Ukrainian Carpaty, 2018)
The pedagogical conditions that ensure the effectiveness of the professional training of future teachers for modeling lessons in the context of variativity of the primary education are identified and theoretically substantiated in the article. The relevance of the designated topic is determined by the need for new pedagogical personnel capable of operating effectively in the context of reforming the primary education system based on the Concept of the New Ukrainian School, using the resource of its variativity when modeling lessons. Thus, by the method of analysis and generalization of the data of psychological and pedagogical scientific literature on the problem, in our study, the following conditions for preparing future teachers for modeling a lesson in the context of the variativity of primary education are highlighted: the organization of the subject-subjective interaction of participants in the educational process, the orientation of the teacher to the introduction of contextual learning technology, enhancing the reflexive position of future teachers of primary school. The essence of the organization of the subject-subjective interaction of the participants of the educational process in the higher educational establishments is revealed, which ensures the transformation of students from passive knowledge consumers into their active seekers, researchers, accomplices. This is especially valuable for their preparation for the implementation of the New Ukrainian School Concept, where partnership pedagogy is defined as a priority. The paper analyzes the effectiveness of the orientation of the teacher on the introduction of contextual learning technology in the formation of the experience of professional activities of modeling the lesson of future primary school teachers. Also the condition for the activation of the students' reflexive position is considered, which ensures that they master the skills of a constructive analysis of the quality of the implementation of the own pedagogical plans and directs them to continuous self-improvement. The combination of the named conditions for the organization of the educational process in a higher educational establishment allows overcoming the inertia of thinking of future primary school teachers, contributes to their ability to simulate lessons (classes) in the context of the variativity of primary education, motivates them to productive pedagogical activities, promotes the development of skills for continuous self-development.